Wartość hodowlana wyselekcjonowanych rodów modrzewia europejskiego (Larix decidua Mill.) z pochodzenia sudeckiego na przykładzie powierzchni doświadczalnej w Zwierzyńcu Lubelskim - Kowalczyk, Jan; Neyko, Ihor (Leśne Prace Badawcze, 2011)
The aim of this study was the preliminary estimation of the breeding value of selected European larch half-sib families based on data from the experimental family trial in Zwierzyniec Lubelski. The trial in Nowiny, Zwierzyniec Forestry District, was established in spring, 2003. The initial spacing was 2.5 by 2.5 m and the forest site code, ‘LMśw’ – fresh mixed broadleaved forest. There were 2948 trees planted originating from 66 families from the region of Jesienik in the Czech eastern Sudeten Mountains. In September 2009, the DBH, height were recorded and wood density was measured using a Pilodyn penetrometer. Stem straightness, crown size and branch angle were scored using the scale from 1 to 5. The mean height of the trees after seven years of growth was 7.57 m. The tallest trees came from family 1414 (8.05 m mean height), and the smallest family was 1709 (6.79 m), a difference of 17% compared with the mean value. The relative differences among families were larger for DBH than for tree height. The overall mean DBH was 10 cm, and the difference between the best and worst performing families was 42% of the mean value. Wood quality did not differ greatly among families, particularly given that there were relatively large differences between individuals. In order to evaluate trees based on a combination of all measured parameters, a selection index was calculated. Based on selection indices, as far as breeding value is concerned, the best families were numbers 1414 and 1411. They demonstrated both good growth and good quality features. The worst families were numbers 1709, 1734 and 1722. They were characterized by weak growth but moderate to good quality features. There was also a statistically-significant positive correlation between survival and the index breeding value of larch families. Those families which grew best were characterized by higher survival rates, which probably resulted from phenotypic selection which eliminates individuals that are poorly-adapted to environmental conditions, thus favouring the best trees, in terms of their growth parameters. The results obtained in this study after seven years of the growth should be considered as preliminary. To estimate the breeding value of the studied larch families a further evaluation is needed when trees reach the age of 15-20 years old.